Utility of severity assessment tools in COVID-19 pneumonia: a multicentre observational study. Issue 1 (2022) - Ahmed, Asim; Alderazi, Sayed A; Aslam, Rumaisa; Barkat, Barooq; Barker, Bethan L; Bhat, Rahul
No abstract available